Facebook Intrusion as a Mediator Between Positive Capital and General Distress: A Cross-Cultural Study - Przepiórka, Aneta; Błachnio, Agata; Sullman, Mark; Gorbaniuk, Oleg; Siu, Nicolson Yat-Fan; Hill, Tetiana; Gras, Maria-Eugenia; Kagialis, Antonios; Lisun, Yanina; Díaz-Peñaloza, Maité; Manrique-Millones, Denisse; Nikiforou, Militsa; et al. (Frontiers in Psychiatry, 2021)
Background: Social networking sites (SNSs) play an important role in many aspects of life nowadays, and it seems to be crucial to explore their impact on human well-being and functioning. The main aim of the study was to examine the mediating role of Facebook intrusion between positive capital and general distress. Posi-tive capital was considered as comprising self-esteem, ego-resiliency, and self-control, while general distress was seen as having three dimensions: depression, anxiety, and stress. Methods: The sample consisted of N = 4,495 participants (M = 22.96 years, SD = 5.46) from 14 countries: Australia, Cyprus, Greece, Hong Kong, Lithuania, New Zealand, Peru, Poland, Russia, Spain, Turkey, the UK, Ukraine, and the USA. We used the following methods: the Facebook Intrusion Questionnaire (FIQ), the Self-Esteem Scale (SES), the Self-Control Scale (SCS), and the Depression, Anxiety, and Stress Scale-21 (DASS-21). Results: We found that Facebook intrusion was a mediator between self-esteem and general distress and between self-control and general distress. Limitations: The present was based on a cross-sectional study and the measures used were self-report measures. The majority of the participants were recruited using convenience sampling. Conclusions: The present findings contribute to a better understanding how the social media have impact on individual mental health. Implications for future study are discussed.